Genome-Wide Identiﬁcation and Expression Proﬁling of the Wnt Gene Family in Three Rice Planthoppers: Sogatella furcifera, Laodelphax striatellus, and Nilaparvata lugens. Issue 5 (9th September 2022) - Peng, Lei; Zhao, Yan
Abstract: The Wnt gene family plays essential roles in regulating many developmental processes, including the maintenance of stem cells, cell division, and cell migration. The number of Wnt genes varies among species. Due to the diversity and importance of their functions, the Wnt gene family has gained extensive research interest in various animal species from invertebrates to vertebrates. However, knowledge of the Wnt gene family is limited in rice planthoppers. Three planthopper species, the white-backed planthopper (Sogatella furcifera Horvath), the small brown planthopper (Laodelphax striatellus Fallén) and the brown planthopper (Nilaparvata lugens Stål) (Hemiptera: Delphacidae), are devastating specialist pests of rice and cause serious damage to rice plants. To better study the evolution and function of the Wnt gene family in rice planthoppers, we identified 8 Wnt family genes in three rice planthoppers with both genomic and extensive transcriptomic resources available. We conducted a systematic analysis of the three kinds of rice planthoppers and analyzed the dynamic patterns of gene conservation, as well as Wnt gene loss and duplication. The expression profiles in different developmental stages of S. furcifera and different adult organs and tissues of L. striatellus provide preliminary functional implications for the Wnt genes in rice planthopper. This study presents the first genome-wide study of the Wnt gene family in rice planthoppers, and our findings provide insights into Wnt function and evolution in rice planthoppers.